1993
DOI: 10.1021/bi00087a030
|View full text |Cite
|
Sign up to set email alerts
|

Modulatory effects on substrate specificity of independent mutations at the serine939/941 position in predicted transmembrane domain 11 of P-glycoproteins

Abstract: The serine residue located at position 939 and 941 in the predicted transmembrane segment 11 of P-glycoprotein (P-gp) encoded by mouse mdr3 and mdr1, respectively, appears to be important for interaction of chemotherapeutic drugs and reversal agents with P-gp. To further understand the role of this residue in this process and to identify the structural requirements involved, we have replaced this serine residue by alanine, cysteine, threonine, tyrosine, tryptophan, and aspartic acid and tested the effect of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

1994
1994
2009
2009

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 41 publications
1
26
0
Order By: Relevance
“…In CHO cells, we showed that expression of the wild-type but not the mutant variants of pfmndrl causes an increased sensitivity to CQ and increased cellular accumulation of a radiolabeled analog of the drug (26). Independent mutations at Ser-939 of Mdr3 (and Mdrl), a position homologous to the Pgh-1 pst 1034 mutation (S1034 -> C1034), have a dramatic effect on the substrate specificity of P-gps, causing either a decrease in resistance to certain drugs or an increase in resistance to others drugs (41,42), but also have a strong effect on the ability of P-gp to complement STE6 (31).These results and other biochemical analyses (5) suggest that TM11 may form part of a substrate binding site in P-gp. Of all the TM domains of P-gp, TM11 is the one that shows the strongest amphipatic character when projected in a a-helical configuration.…”
Section: Discussionmentioning
confidence: 99%
“…In CHO cells, we showed that expression of the wild-type but not the mutant variants of pfmndrl causes an increased sensitivity to CQ and increased cellular accumulation of a radiolabeled analog of the drug (26). Independent mutations at Ser-939 of Mdr3 (and Mdrl), a position homologous to the Pgh-1 pst 1034 mutation (S1034 -> C1034), have a dramatic effect on the substrate specificity of P-gps, causing either a decrease in resistance to certain drugs or an increase in resistance to others drugs (41,42), but also have a strong effect on the ability of P-gp to complement STE6 (31).These results and other biochemical analyses (5) suggest that TM11 may form part of a substrate binding site in P-gp. Of all the TM domains of P-gp, TM11 is the one that shows the strongest amphipatic character when projected in a a-helical configuration.…”
Section: Discussionmentioning
confidence: 99%
“…Altering this Ser-939 residue similarly abolishes the ability of mdr3 to complement ste6. This change to a phenylalanine residue at position 939 in mdr3 has been associated with dramatic changes in the substrate specificity of this gene product in mammalian systems (32)(33)(34). These The observation that residues in transmembrane domain regions determine the specificity and level of resistance to different drugs, as well as the hydrophobic nature of the compounds which the mdr genes transport, leads to a current model which views drug transport as a biphasic process involving partitioning into the membrane followed by transport across it (35).…”
Section: Resultsmentioning
confidence: 99%
“…The sample was extracted with phenol/chloroform, and the cDNA was precipitated with ethanol. PCR amplification of the cDNA was carried out using a primer (P2) that overlaps another portion of exon 2, GGGAAGAGCAGACAAGAACT-TCTCGAAGATG, and the primer (P3), GCTCTAGACTCGAGTCGA-CATCGT 17 . The PCR product was purified by agarose gel electrophoresis and evaluated by direct DNA sequencing using primer P2 (fmol DNA Sequencing System; Promega, Madison, WI).…”
Section: Methodsmentioning
confidence: 99%
“…There has been considerable effort invested in the characterization of drug resistance changes caused by Pgp mutations (11). Mutations that have arisen in cultured cells selected for resistance to specific drugs (12)(13)(14) and mutations introduced by site-directed mutagenesis have been evaluated (10,(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32). In many cases, the resistance to one drug may increase while the resistance to others either changes or remains the same.…”
Section: P-glycoprotein (Pgp)mentioning
confidence: 99%
See 1 more Smart Citation